PELATIHAN PEMBUATAN PANGANAN SEHAT 'WAJIK JAGUNG' BERBAHAN LOKAL (Zea mays) DAN PEMASARANNYA - Gertreda Latumakulita; Lodowik Landi Pote; Helena Hepa Lengari; Grace Rianti Latuheru (Aptekmas Jurnal Pengabdian pada Masyarakat, 2023)
This community service activity titled "Training in Production and Marketing of Healthy Snacks 'Wajik Jagung' Made from Local Ingredients (Zea mays)" aims to (1) Process maize (Zea mays) into a healthy snack 'Wajik Jagung' and market it to increase community income. (2) To serve as an alternative innovation in the processing and utilisation of the agricultural products of the villagers into value-added products. The specific objective to be attained from the implementation of this activity is to improve the welfare of the community, namely the Bethel Indonesia Church community. The method of implementing this activity is process skills. The procedure for the implementation of this activity is: strengthening meeting of activity plans with activity partners to be carried out directly, preparing facilities and infrastructure as well as materials for the implementation of activities, and the implementation of production activities. Healthy snack 'Wajik Jagung' is the product to be produced. These activities are carried out at GBI Bunga Bakung. Corn owned by GBI Bunga Bakung community is the raw material for production. The production of a technology for processing corn into healthy snacks is the output of this activity.